Determinants of Capital Structure of UK Quoted Companies - Paulauskas, Justas (2008)
This paper investigates the determinants of capital structure in UK, seeks to determine, which capital structure theory is more applicable to UK companies, and intends to compare UK findings with previous empirical literature. Five determinants of capital structure, namely firm size, asset tangibility, profitability, growth opportunities and non-debt tax shields, are used in the research. Panel data set of 446 UK public quoted companies during 1998-2007 period is employed. Research methodology encompasses the use of several multiple regression models, namely regression with industry dummies to measure the importance of industry effects in explaining debt ratios, pooled panel OLS regression, and fixed/random effects panel data regression that accounts for firm-specific time-invariant heterogeneity in the data. Additionally, time dummies are added in each regression to include for sample-wide macroeconomic shocks. Each model is tested using both book debt and market debt ratios. The leverage is found to be determined by firm size (+), asset tangibility (+), profitability (-) and growth opportunities (-). A very weak negative effect of non-debt tax shields is also found. Up to 36% of variance in leverage is found to be explained by industry effects. Pooled OLS model can explain up to 49% of variance in leverage. Fixed/random effects model describes up to 27% of variance in leverage. The results are found to be generally robust not only to the method of estimation, which confirms that the same determinants affect debt ratios both within and between firms, but also to alternative definitions of leverage and alternative proxies for the determinants of capital structure. No conclusive evidence is found that one single theory can explain the differences in capital structure in UK better than another. Both pooled OLS and fixed/random effects models provide similarly mixed and inconclusive results. Nevertheless, the findings on UK companies compare favourably to most of the previous empirical tests. The negative link between leverage and profitability remains the main puzzle for the supporters of the trade-off theory. Moreover, limitations of the research are recognised and recommendations for future research are made.